Is farmers' agricultural production a carbon sink or source? – Variable system boundary and household survey data. (1st September 2020) - Chen, Ru; Zhang, Ruoyan; Han, Hongyun; Jiang, Zhide
Abstract: The widespread and scattered smallholders in China have a profound impact on agricultural production in response to climate change. Using the data of peasant household obtained from survey and the factor coefficients collected in Shaanxi Province of China, the carbon footprint (CF) of farmer's agricultural production (FAP) was estimated by a multi system boundary scenarios approach to judge the contribution of FAP for climate change reasonably. The results showed that the agricultural activities' carbon footprint (ACF), farm's carbon footprint (FCF) and product's carbon footprint (PCF) of wheat, maize, rice and apple crops in FAP exhibited significant differences in four scenarios, and the positive climate externalities of FAP rely on its own duality of carbon effect. Distribution structure of ACF in FAP subsystem under the four scenarios indicated that allocation of emission responsibility has a significant impact on the carbon effect of FAP. The categories of key source in FAP were greenhouse gas emissions from heterotrophic soil respiration in agro-ecosystem (AE), chemical fertilizer in raw material production system (RMPS), diesel or gasoline in RMPS and agricultural production system and direct N2 O emissions in AE, and the key sink categories were carbon sequestration from crop biomass and cropland management in AE. Therefore, the ecological benefits should be embedded in the economic benefit-oriented agricultural production policy objectives, in order to reduce the dependence on high energy-consuming industrial products in FAP, optimize the agricultural industrial structure and guide farmers from cleaner production behavior. Besides, the uncertainties of CF accounting method drop significantly which we improved by integrating carbon-nitrogen cycle into life cycle assessment theory. Graphical abstract: Image 1 Highlights: Carbon-nitrogen cycle included in life cycle assessment to improve the system boundary. Cross-contrast analysis used on carbon footprints in farmer's agricultural production. Positive climate externalities of agriculture depend on the duality of carbon effect. It has a great mitigation potential to guide farmers' cleaner production behavior. Both economy and environment consideration cost-effectively optimizes policy objectives.